2009
DOI: 10.1590/s1517-83822009000200027
|View full text |Cite
|
Sign up to set email alerts
|

Use of Bacillus pumilus CBMAI 0008 and Paenibacillus sp. CBMAI 868 for colour removal from paper mill effluent

Abstract: Bacillus pumilus and Paenibacillus sp. were applied on the paper mill effluent to investigate the colour remotion. Inocula were individually applied in effluent at pH 7.0, 9.0 and 11.0. The real colour and COD remotion after 48h at pH 9.0 were, respectively, 41.87% and 22.08% for B. pumilus treatment and 42.30% and 22.89% for Paenibacillus sp. Gel permeation chromatography was used to verify the molar masses of compounds in the non-treated and treated effluent, showing a decrease in the compounds responsible f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 10 publications
(18 reference statements)
1
9
0
Order By: Relevance
“…Decolorization of pulp and paper mill effluent due to Xylanase in B. pumilus CBMAI 0008 and MnP in Paenibacillus sp. CBMAI 868 is reported in previous studies (Moriya et al 2005;Oliveira et al 2009). …”
Section: Enzymes Involved In Decolorization and Delignification Processmentioning
confidence: 66%
“…Decolorization of pulp and paper mill effluent due to Xylanase in B. pumilus CBMAI 0008 and MnP in Paenibacillus sp. CBMAI 868 is reported in previous studies (Moriya et al 2005;Oliveira et al 2009). …”
Section: Enzymes Involved In Decolorization and Delignification Processmentioning
confidence: 66%
“…Prabu and Udayasoorian (2005) reported that white rot fungus that was isolated from soil samples, enriched by continuous pulp and paper mill effluent irrigation, and identified as P. chrysosporium, was capable of 79% COD reduction. De Olivera et al (2009) evaluated the ability of Bacillus pumilus CBMAI0008 to produce alkaline enzymes when isolated from wood decomposition and Paenibacillus sp. CBMAI 868 production ability when isolated from pulp and paper mill wastewater to produce alkaline enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…isolated from paper mill effluent (22) were able to produce MnP in alkaline conditions. These enzymes were able to remove the color from paper mill effluent (23). In this study, we report on the purification and partial characterization of MnP from B. pumilus and Paenibacillus sp.…”
mentioning
confidence: 99%